Rethinking National Identities in Divided Societies of Post-Ottoman Lands: Lessons from Lebanon and Cyprus - Duba, Gulay Umaner; Nur Köprülü (European Journal of Multidisciplinary Studies, 2017)
The communal identities rooted in the millet system are still salient in post-Ottoman lands. Cyprus and Lebanon offer two cases where ethnic and sectarian identities are more prominent than national identities. In this respect both countries represent highly divided societies in post-Ottoman territories. This article discusses the failure of power-sharing systems in Cyprus and Lebanon, arguing that the lack of cultivation of a common national identity at the founding of these republics remains even today a central obstacle to implementing stable multinational/sectarian democratic systems. As a part of Greater Syria, today’s Lebanon is a homeland to many ethnic and sectarian communities. Lebanese politics historically has been governed by a system of consociationalism, which prevents any one group from dominating the political system. This system of power sharing dates back to the 1943 National Pact, and as a result of the sectarian nature of this arrangement, religious communal identities have a stronger pull than a Lebanese national identity. These communal identities crystallized over the course of a 14-year civil war, and were exacerbated by the assassination of former Prime Minister Rafiq al-Hariri in 2005. In the case of Cyprus, the possibility of cultivating a shared national identity between Turkish Cypriots and Greek Cypriots has historically been suppressed by kin-state relations and colonial policies which have, in turn, resulted in inter-communal conflict. An understanding of this conflict and the nature of the nationalisms of each community helps explain how the 1960 Constitution of a bi-communal and consociational Republic of Cyprus hindered inter-communal relations – a precondition for the cultivation of a common national identity – and ultimately failed. From enosis to taksimto the April 2004 referendum on the UN’sAnnan Plan, the contentious interaction between external constraints and collective self-identification processes subsequently reinforced ethno-religious identifications. Through an examination of such processes, this article aims to identify and illuminate the shifting forces that shape deeply divided societies in general, and that have shaped Cyprus and Lebanon in particular. Understanding such forces may help break down barriers to the development of common national narratives.